Targeting the FAK-Src Complex in Desmoplastic Small Round Cell Tumors, Ewing Sarcoma, and Rhabdomyosarcoma. (12th May 2022) - van Erp, Anke E. M.; Hillebrandt-Roeffen, Melissa H. S.; van Bree, Niek F. H. N.; Plüm, Tim A.; Flucke, Uta. E.; Desar, Ingrid M. E.; Fleuren, Emmy D. G.; van der Graaf, Winette T. A.; Versleijen-Jonkers, Yvonne M. H.
Abstract : Desmoplastic small round cell tumors (DSRCTs), Ewing sarcoma (ES), and alveolar and embryonal rhabdomyosarcoma (ARMS and ERMS) are malignant sarcomas typically occurring at young age, with a poor prognosis in the metastatic setting. New treatment options are necessary. Src family kinase inhibitor dasatinib single-agent treatment has been investigated in a phase 2 study in patients with advanced sarcomas including ES and RMS but failed as a single agent in these subtypes. Since previous studies demonstrated high FAK and Src activities in RMS and ES tissue and cell lines, and dasatinib treatment was shown to upregulate activated FAK, we hypothesized that FAK-Src combination treatment could potentially be an interesting treatment option for these tumor types. We examined the effects of targeting the FAK-Src complex by addressing (p)FAK and (p)Src expressions in tumor sections of DSRCT ( n  = 13), ES ( n  = 68), ARMS ( n  = 21), and ERMS ( n  = 39) and by determining the antitumor effects of single and combined treatment with FAK inhibitor defactinib and multikinase (Abl/SFK) inhibitor dasatinib in vitro on cell lines of each subtype. In vivo effects were assessed in DSRCT and ERMS models. Concurrent pFAK and pSrc expressions (H-score >50) were observed in DSRCT (67%), ES (6%), ARMS (35%), and ERMS (19%) samples. Defactinib treatment decreased pFAK expression and reduced cell viability in all subtypes. Dasatinib treatment decreased pSrc expression and cell viability in each subtype. Combination treatment led to a complete reduction in pFAK and pSrc in each cell line and showed enhanced cell viability reduction, drug synergy, DNA damage induction, and a trend toward higher apoptosis induction in DSRCT, ERMS, and ARMS but not in ES cells. These promising in vitro results unfortunately do not translate into promising in vivo results as we did not observe a significant effect on tumor volume in vivo, and the combination did not show superior effects compared to dasatinib single-agent treatment.